Metode Dakwah Al-Habib Syech Bin Muhammad Assegaf di Dusun Pulau Kerakap Kecamatan Pelayang Kabupaten Bungo - Ranny Eliaviani; Penmardianto Penmardianto (Universitas Pahlawan Tuanku Tambusai, 2023)
Da'wah in Islam is an obligation for every adherent. In carrying out da'wah, it must be conveyed using the correct method, so that the da'wah message is easily accepted by mad'u. The da'wah method carried out by Al-Habib Syech Bin Muhammad Assegaf has an important role for the Islamic development of the community in Pulau Kerakap Hamlet, because before the arrival of Al-Habib Syech Bin Muhammad Assegaf the understanding of the religion of the residents of Pulau Kerakap Hamlet was still lay, abangan, there was still a lack of activities religious activities carried out by residents of Pulau Kerakap Hamlet, but since the arrival of Al-Habib Syech Bin Muhammad Assegaf many religious activities have been carried out by residents and many residents have started to participate in religious activities. The da'wah method that Al-Habib Syech Bin Muhammad Assegaf uses is the da'wah bil-hikmah method, taking into account the situation and condition of his mad'u. Prioritizing policies and approaching their mad'u. As for the mau'izatul hasanah method by giving advice in polite and gentle language using five elements, namely advice (suggestions), tabsyir (good news), tanzir (warnings), wills and stories. Habib Syech bin Muhammad Assegaf in preaching experienced several obstacles such as: mechanical obstacles, due to interference with communication tools or media such as sound systems and loudspeakers that were not good. Socio-anthropological barriers occur because of the condition of people who have different levels of diversity, lifestyles and habits. Psychological barriers, which are caused by external factors communicators who have bad prejudice against preachers and finally, namely ecological barriers related to natural events. Keywords: Da'wah Method; Da'wah obstacles; Al-Habib Syech Bin Muhammad Assegaf